Assessment of Eating Attitude and Psychiatric Parameters in Patients with Acne Vulgaris - Hazel Ezgi Kaya; İlknur Kıvanç Altunay; Aslı Aksu (Dermatology Practical & Conceptual)
Introduction: Redundancy of psychological comorbidities in acne vulgaris may contribute to disturbed eating attitude.